2010
DOI: 10.1111/j.1464-410x.2010.09696.x
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral resection of bladder tumour complicated by perforation requiring open surgical repair – clinical characteristics and oncological outcomes

Abstract: Study Type – Therapy (case series)
Level of Evidence 4 What’s known on the subject? and What does the study add? Evidence suggests that open repair of a bladder perforation during TURBT may increase the risk of pelvic or distant disease recurrence. The study demonstrates that while bladder violation during TURBT may carry a potential for considerable morbidity, it does not seem to substantially increase the risk of extravesical tumour seeding and disease recurrence. OBJECTIVE • To examine the clinical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
2
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 11 publications
1
60
2
13
Order By: Relevance
“…The incidence of bladder perforation is suspected of being higher than reported [4]. However, bladder perforation caused by transurethral resection rarely requires surgical treatment.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The incidence of bladder perforation is suspected of being higher than reported [4]. However, bladder perforation caused by transurethral resection rarely requires surgical treatment.…”
Section: Discussionmentioning
confidence: 92%
“…In the present case, the size of the tumor was fairly large (3.8 cm), and the patient was elderly (80 years) and had undergone three prior TURB surgeries. In addition, the tumor was spread over the entire bladder, putting the patient at high risk group for bladder perforation that could require surgical treatment [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Golan et al 1 also presented a recent review of 4144 TURBT patients, of which 15 had bladder perforations and two had extravesical recurrence. In a comparative study, patients with bladder cancer with perforation showed a trend towards an increase in recurrence and progression and a decrease in survival 10.…”
Section: Discussionmentioning
confidence: 99%
“…Perforation can also delay the time to complete resection and prevent immediate intravesical chemotherapy—both of which may increase the likelihood of recurrence, progression and metastasis. There are relatively few clinical reports of extravesical recurrence from seeding 1 4 5 10. We report on a rare case of extravesical recurrence in the left paracolic gutter in a 61-year-old woman who underwent a TURBT for non-muscle invasive urothelial carcinoma complicated by intraperitoneal bladder perforation and open repair.…”
Section: Introductionmentioning
confidence: 95%